Pemanfaatan Tanah Kas Desa Tatung Kecamatan Balong Kabupaten Ponorogo Dengan Sistem Lelang Tanah - Sari, Nova Permata; Nasution, Robby Darwis (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Town resources can be as Town depository lands, standard land, town markets, creature markets, boat moorings, town structures, fish barters, farming item barters, town claimed woods, town springs, public showers, and different resources having a place with the Town people group. Town land is town possessed land that can be utilized for town pay and for the government assistance of the town local area. This examination was directed to perceive how the utilization of town depository lands and the interaction of land closeout in Tatung Town, Balong Ponorogo Region. Questions that emerge in this investigation are the manner by which the Tatung Town Government, Balong Locale, Ponorogo Rule oversees town depository grounds and how the land sell off measure in Tatung Town Balong Region, Ponorogo Rule. This examination utilized a subjective graphic exploration strategy. The land closeout framework in Tatung Town, Balong Locale, Ponorogo Rule can improve the way of life of the Town people group where with the town depository land sell off framework, individuals who don't have farming area can oversee land, yet the sale interaction has not been done such that right and open so lawful issues don't emerge later on and there is no maltreatment of force and authority by the town government, so in the town of Tatung there is a requirement for socialization and heading to the local area and town government in regards to the right land sell off measure.